An experimental investigation of top–down effects of consumer diversity on producer temporal stability. (17th September 2018) - Valone, Thomas J.; Balaban‐Feld, Jesse
Abstract: In multitrophic systems, the diversity of consumers can affect the abundances and temporal stability of the species they consume via 'top‐down' effects. However, little is known about how variation in consumer functional diversity affects the temporal stability of aggregate producer communities. We use data from a long‐term experiment to determine how variation in rodent granivore functional richness affected the temporal stability of the annual plant communities whose seeds they consume. Experimental plots excluded either all granivorous rodents, just large‐bodied kangaroo rat granivores, or no rodents. Over the 11‐year period studied, reductions in rodent granivory resulted in higher annual plant community abundance and higher abundance of exotic Erodium cicutarium, but lower annual plant species richness and diversity. However, there was no effect of the consumer experimental treatments on annual plant community temporal stability. Synthesis . The loss of consumers from an ecosystem need not necessarily destabilize the producer community, even when loss of consumers results in reduced producer richness and diversity. Abstract : The loss of consumers from an ecosystem need not necessarily destabilize the producer community, even when loss of consumers results in reduced producer richness and diversity.